2023
DOI: 10.3390/polym15051202
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctionalization and Applications of Polymeric Nanofibers in Tissue Engineering and Regenerative Medicine

Abstract: The limited ability of most human tissues to regenerate has necessitated the interventions namely autograft and allograft, both of which carry the limitations of its own. An alternative to such interventions could be the capability to regenerate the tissue in vivo.Regeneration of tissue using the innate capacity of the cells to regenerate is studied under the discipline of tissue engineering and regenerative medicine (TERM). Besides the cells and growth-controlling bioactives, scaffolds play the central role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 193 publications
0
15
0
Order By: Relevance
“…The crosslinking of ECM proteins to the surface of nanofibers can lead to better results in terms of the scaffold's mechanical and biological functions. [23,24] In this regard, Lee et al Showed that the crosslinking of gelatin to Polycaprolactone (PCL) nanofibrils enhanced cellular attachments. [25] In a similar approach by Li et al, it was found that the surface modification of nanofibers with hyaluronic acid in an in vivo model could increase migration and attachments of host endothelial cells, resulting in improved angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crosslinking of ECM proteins to the surface of nanofibers can lead to better results in terms of the scaffold's mechanical and biological functions. [23,24] In this regard, Lee et al Showed that the crosslinking of gelatin to Polycaprolactone (PCL) nanofibrils enhanced cellular attachments. [25] In a similar approach by Li et al, it was found that the surface modification of nanofibers with hyaluronic acid in an in vivo model could increase migration and attachments of host endothelial cells, resulting in improved angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The crosslinking of ECM proteins to the surface of nanofibers can lead to better results in terms of the scaffold's mechanical and biological functions. [ 23,24 ] In this regard, Lee et al. Showed that the crosslinking of gelatin to Polycaprolactone (PCL) nanofibrils enhanced cellular attachments.…”
Section: Discussionmentioning
confidence: 99%
“…Biofunctionalization of tissue engineering materials improves cellular interaction and tissue integration. Currently, a large number of functionalization methods of tissue engineering materials are known, ranging from single peptides and components of ECM, including enzymes responsible for its remodeling, to decellularization of tissues and whole organs, which is described in detail in the reviews [ 158 , 178 – 180 ]. The success of the approach to obtain ECM secreted by a specific cell type, such as MSC, can be assessed based on recent studies in this area [ 181 183 ].…”
Section: Potential Therapeutic Strategies Targeting Ecm-induced Signa...mentioning
confidence: 99%
“…Nanofibers, both natural and synthesized, show great promise as nanofillers to improve the tensile properties of a variety of polymeric systems. [1][2][3] Most of the work on nanofibers so far has focused on developing new synthetic methods, many of which are not suited to large scale synthesis. For example, electrospinning is used to synthesize nanofibers, but scalingup for industrial applications has proved challenging due to low yield 4 and variable quality.…”
Section: Introductionmentioning
confidence: 99%